2015
DOI: 10.1002/mrd.22495
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of monoclonal non‐specific suppressor factor beta (MNSFB) promotes pregnancy loss in mice

Abstract: Maternal immune tolerance to the semi-allogenic fetus is required for successful pregnancy in mammals. Monoclonal nonspecific suppressor factor beta (MNSFB) is an immunosuppressive factor present in uterine epithelial and stromal cells, as well as in macrophages and T cells. Although the functional neutralization of MNSFB using specific antibodies against it lead to failed embryo implantation in mice, the exact role of MNSFB at the fetal-maternal interface remains unclear. The present study generated condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…Mnsf-beta +/− mice (Gu, He et al, 2015). As expected, uterine NDRG1 expression was significantly decreased in the mifepristone-induced pregnancy loss mice (Figure 4a).…”
Section: And Heterozygoussupporting
confidence: 78%
See 3 more Smart Citations
“…Mnsf-beta +/− mice (Gu, He et al, 2015). As expected, uterine NDRG1 expression was significantly decreased in the mifepristone-induced pregnancy loss mice (Figure 4a).…”
Section: And Heterozygoussupporting
confidence: 78%
“…In our previous studies, two pregnancy loss models were established in mice as follows: one is the mifepristone (RU486)‐treated mouse model (Yang, Yu et al, ), and the other is the monoclonal nonspecific suppressor factor ( MNSF ) ‐beta deficiency mouse model (Gu, He et al, ). Pregnant mice were treated with RU486 (25 μg per mouse) on Day 8 of pregnancy (D8), and the uterine tissues were collected on Day 10 of pregnancy (D10, n = 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, roles of MNSFβ in cell apoptosis were also demonstrated [10, 11]. In our previous studies, a decreased MNSFβ expression was observed in decidual tissues of RM patients [12], and it was also found that immunoneutralization of MNSFβ inhibited the mouse embryo implantation [13] and the reduced uterine MNSFβ expression in heterozygous MNSFβ-deficient ( MNSFβ +/− ) female mice caused the early pregnancy loss, suggesting that MNSFβ plays a key role at the maternal-fetal interface during the pregnancy process in mice [12].…”
Section: Introductionmentioning
confidence: 99%